Palynology and organic petrography of the Tyler Formation (lower Pennsylvanian), Williston Basin, North Dakota, USA. (3rd April 2021) - Pocknall, David; Thomas, Marie; Melville, Ethan; Demchuk, Thomas
Abstract: The palynoflora and organic petrography of core samples from the Tyler Formation in the Williston Basin, North Dakota, USA were evaluated to determine their age and depositional environment. The palynofloras are assigned to seven plant groups used by previous authors who studied Carboniferous floras. Lycopsid trees, represented by Lycospora species and Crassispora kosankei are the most abundant and well-preserved miospores recorded. Palynomorphs representing small lycopsids, calamites, cordaites, and conifers, comprise a relatively minor part of the palynoflora. The petrographic component from seven coeval coal samples contain moderate to high mineral content and macerals which are dominated by vitrinite (woody components) and to a lesser extent inertinite and liptinite (lipid-rich plant material). Common vitrinite macerals include collotelinite and collodetrinite, and semifusinite and minor fusinite representing inertinite macerals. The palynofloras are of Early Pennsylvanian age, based on the presence of the age-significant fossils Schulzospora rara and Cirratriradites saturnii together with abundant Lycospora spp. The palynoflora and petrographic data suggest that the Tyler Formation in this location was deposited in a fluvially-dominated delta with some tidal influence. Wet, stagnant anoxic environments (coal swamps) were frequently flooded with clastic material from a fluvial source. Macerals, especially inertinite, imply periods of subaerial exposure, fire, or highly oxygenated waters, and liptinite (lipid-rich plant material), suggests periodic drowning of the coal swamp and formation of shallow lacustrine paleoenvironments.